Pengaruh Penaklukan Konstantinopel Terhadap Kemajuan Turki Usmani Tahun 1453 ( Kajian Politik Ekspansi Sultan Muhammad Al-Fatih) - Rulianto Rulianto; Altin Dokopati (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2021)
The purpose of this study is (1). To find out about the conditions of the ottoman turks before conquering Constantinople (2). To find out about the political progress and the ottoman military in the time of Sultan Muhammad Al-Fatih (3). To find out the influence of constantinople’s conquest on the progress of Ottoman turks in 1453. This type of research is descriptive qualitative, and using the library research method one method of data processing which is done by systematically compiling so that general conclusions can be obtained. The result of this study was the influence of Constantinople’s conquest of the progress of Ottoman Turkey in 1453. The city of Constantinople as a country that is so strong lies in the territory of Byzantium. Efforts to conquer this region continue to be carried out from the time Umayyah, Abbasiyah, arrived at the time of Ottoman rule. The conquest could be carried out on the 20th of Jumadil early 857 H/ mei 291453 M, at 1.00 am, Tuesday, the main attack was launched. The mujahideen were ordered to raise the voice of the takbir while attacking the city. The population of Constantinople was at the height of its fear that morning. Mujahideen who are determined to fight in the cause of Allah, so brave to invade the crusaders in the city. In the end the city of Constantinople could be conquered by Sultan Muhammad Al-Fatih with his troops. It nrought great influence to the Ottoman Turks in the field of military political, economy, governance, of religious and cultural science, and expanding to Europe.